The FRB 20121102A November rain in 2018 observed with the Arecibo Telescope. Issue 1 (25th November 2022) - Jahns, J N; Spitler, L G; Nimmo, K; Hewitt, D M; Snelders, M P; Seymour, A; Hessels, J W T; Gourdji, K; Michilli, D; Hilmarsson, G H
ABSTRACT: We present 849 new bursts from FRB 20121102A detected with the 305-m Arecibo Telescope. Observations were conducted as part of our regular campaign to monitor activity and evolution of burst properties. The 10 reported observations were carried out between 1150 and $1730\, {\rm MHz}$ and fall in the active period around 2018 November. All bursts were dedispersed at the same dispersion measure and are consistent with a single value of $(562.4 ± 0.1)\, {\rm pc\, cm^{-3}}$ . The rate varies between 0 bursts and 218 ± 16 bursts per hour, the highest rate observed to date. The times between consecutive bursts show a bimodal distribution. We find that a Poisson process with varying rate best describes arrival times with separations ${\gt}{0.1\, {\rm s}}$ . Clustering on time-scales of $22\, {\rm ms}$ reflects a characteristic time-scale of the source and possibly the emission mechanism. We analyse the spectro-temporal structure of the bursts by fitting 2D Gaussians with a temporal drift to each sub-burst in the dynamic spectra. We find a linear relationship between the sub-burst's drift and its duration. At the same time, the drifts are consistent with coming from the sad-trombone effect. This has not been predicted by current models. The energy distribution shows an excess of high-energy bursts and is insufficiently modelled by a single power law even within single observations. We find long-term changes in the energy distribution, the average spectrum, and the sad-trombone drift, compared to earlier and later published observations. Despite the large burst rate, we find no strict short-term periodicity.